The European Migration Crisis in the Benelux countries - Galina M. Sidorova (Современная Европа)
The article is dedicated to one of the key problems of our time – migration processes in Europe and their consequences on the example of the Benelux countries. The purpose of the study is to identify the features of the migration policy of the Benelux countries in recent years, the mechanisms of their regulatory and legal system, capable or unable to regulate migration processes. Using the comparative-institutional method, as well as event analysis, the trends of migration in this region as a recipient of a significant influx of emigrants and refugees, are shown. Attention is focused on the common and distinctive features of the migration policy of Belgium, the Netherlands and Luxembourg. The author notes the generally liberal approach of the Benelux countries to solving the problem, which to a certain extent damages their national interests, creates social and humanitarian problems. The authorities of these countries are faced with an increase in migration from Muslim countries and their religious attitudes, the refugee crisis, and issues of social adaptation and integration of migrants. Immigration processes are accompanied by an increase in crime, destabilization of the internal situation, and discontent of the local population. The authorities are forced to periodically review their political and diplomatic tools, adapt and modify them in order to reduce the number of illegal migrants and the risks of renewed conflicts on ethnic and religious grounds. The author relied on the works of domestic and foreign authors, statistical information of European migration services, as well as information from international experts in this field. As a result, the characteristics of the migration policy of the countries under study are given, the consequences of mass migrations are determined. The author substantiates the conclusion that the solution to the migration issue in the Benelux countries is not visible in the near future, despite the coordinated efforts of their security structures. Effective management of migration and mitigation of negative consequences have yet to be developed and put into practice.